Simulation on Collective Panic Behavior Based on PI - ZHENG, Wen; ZHU, Da (Discoveries in Agriculture and Food Sciences, 2019)
The collective panic behavior, which is caused by PI (Propagation Intensity), influences the welfare of citizens and the stability of the society (business). A well-known challenge is to understand the spreading mechanism of the panic behavior. In this work, the PI is classified as and , defined in the coefficient (Promotion Intensity) and (Inhibition Intensity) in the probability. MAS (multi-agent-simulation) model/tool is used to construct the systematic structure composed of four types of the participants (the individuals, the mass media, the social leaders, and the supervisors).This tool stimulates the collective panic behavior from the initial coefficient and , showing the different results in the condition of the population size and the conformity. Through setting up the rules and the strategies in an emergency, the framework stimulates the interaction between the agents (e.g. between the individuals, between the individuals and the mass media, between the individuals and the social leaders, between the individuals and the supervisors). The results advocate that the current simulator might be an appropriate first step towards the simulation and analysis of the combination of rules and strategies in panic behavior.